Interlocutors’ Responses to The Realization of Positive Politeness Strategies in Classroom Discussion Through Online Media - Dian aprianti; Januarius Mujiyanto; Issy Yuliasri (Universitas Negeri Semarang, 2022)
The education sector is one affected by the pandemic. The teachers and students are encouraged to conduct teaching and learning through online media. It is assumed that online learning involves the Politeness of students' utterances. Moreover, online learning brings out the characteristics of the realization of positive politeness strategies during the discussion. This study used Brown and Levinson's (1987) theory to investigate the realization of positive politeness strategies in the classroom discussion through online media by Pascasarjana Students at Universitas Negeri Semarang and the relationship between positive politeness strategies and interlocutors' responses. In addition, it used Levinson's (1983) theory to investigate the interlocutors' responses to politeness strategies. This research uses qualitative research with the data from the utterances during classroom discussion during a semester by Pascasarjana students in the 2019/2020 academic year. Transcription of speech data follows Sacks' transcription symbols (1998). The findings reveal the realization of fifteen positive politeness strategies. They also show the relation between the positive politeness strategies taken and the interlocutors' responses, categorized into preferred and dispreferred reactions. In contribution to the education sector, this study provides benefits for increasing students' understanding regarding the use of positive Politeness and interlocutors' responses, especially in Pragmatics. Moreover, the students are expected to create valuable communication. In addition, the study also benefits the student's comprehension of the factors that influence the relationship between positive politeness strategies and interlocutors' responses.